Metabolic Aspects of Migraine: Association With Obesity and Diabetes Mellitus - Rivera-Mancilla, Eduardo; Al-Hassany, Linda; Villalón, Carlos M.; MaassenVanDenBrink, Antoinette (Frontiers in Neurology, 2021)
Migraine is a disabling neurovascular disorder, characterized by moderate to severe unilateral headaches, nausea, photophobia and/or phonophobia, with a higher prevalence in women than in men, which can drastically affect the quality of life of migraine patients. In addition, this chronic disorder is related with metabolic comorbidities associated with the patient's lifestyle, including obesity and diabetes mellitus (DM). Beyond the personal and socioeconomic impact caused by migraine, obesity and DM, it has been suggested that these metabolic disorders seem to be related to migraine since: (i) they are a risk factor for developing cardiovascular disorders or chronic diseases; (ii) they can be influenced by genetic and environmental risk factors; and (iii) while clinical and epidemiological studies suggest that obesity is a risk factor for migraine, DM (i.e. type 1 and type 2 DM) have been reported to be either a protective or a risk factor in migraine. On this basis, and given the high worldwide prevalence of migraine, obesity and DM, this article provides a narrative review of the current literature related to the association between the etiology and (patho)physiology of migraine and these metabolic disorders, considering lifestyle aspects, as well as the possible involvement of neurotransmitters, neuropeptides, and/or sex hormones. While a link between migraine and metabolic disorders has been suggested, many studies are contradictory and the mechanisms involved in this association are not yet sufficiently established. Therefore, further research should be focused on understanding the possible mechanisms involved.